91.4k views
4 votes
Find the polynomial. 2(3y − 1)(y − 3) is the factored form of

User Pushkr
by
5.2k points

2 Answers

3 votes
First, multiply (3y-1) by 2 using distributive property
2(3y - 1)(y - 3)
= (2 × 3y - 2 × 1)(y - 3)
= (6y - 2)(y - 3)

Second multiply (6y - 2) by (y - 3) also using distributive property
(6y - 2)(y - 3)
= (6y)(y) - 2(y) - 3(6y) - 2(-3)
= 6y² - 2y - 18y + 6
= 6y² - 20y + 6

The polynomial form is 6y² - 20y + 6
User MMALSELEK
by
5.7k points
1 vote
6y²-20y+6 Not sure on this one but gave it a good guess!

User RishiKesh Pathak
by
5.5k points